Analisis Keamanan Komputer dalam Melindungi Data dari Serangan Siber - Farras Ajeng Ananta; Airin Wulandary; Jumra Rizka; Wahyu Abdillah Hidayat; Muhammad Azkal (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid advancement of information technology has made humans increasingly dependent on computer systems in various aspects of daily life. However, this situation is also accompanied by an increased risk of security threats, such as digital attacks that can disrupt system operations and cause data breaches. Computer security becomes a crucial element to maintain the confidentiality, integrity, and accessibility of information. This study aims to examine the concept of computer security, various types of common threats, and protection strategies that can be implemented to protect data from cyber threats. The research approach applied is a literature review through examination of academic journals, books, and articles related to computer security. The research findings reveal that the implementation of security mechanisms such as antivirus software, firewalls, data encryption, and increasing user awareness can reduce the risk of cyber attacks. The conclusion of this study is that computer security needs to be implemented comprehensively, both from technical and non-technical sides, so that the system is maximally protected.